Insulation Characteristics of Sisal Fibre/Epoxy Composites - A. Shalwan; M. Alajmi; A. Alajmi (International Journal of Polymer Science)
Using natural fibres in civil engineering is the aim of many industrial and academics sectors to overcome the impact of synthetic fibres on environments. One of the potential applications of natural fibres composites is to be implemented in insulation components. Thermal behaviour of polymer composites based on natural fibres is recent ongoing research. In this article, thermal characteristics of sisal fibre reinforced epoxy composites are evaluated for treated and untreated fibres considering different volume fractions of 0–30%. The results revealed that the increase in the fibre volume fraction increased the insulation performance of the composites for both treated and untreated fibres. More than 200% insulation rate was achieved at the volume fraction of 20% of treated sisal fibres. Untreated fibres showed about 400% insulation rate; however, it is not recommended to use untreated fibres from mechanical point of view. The results indicated that there is potential of using the developed composites for insulation purposes.